The Quality and Composition of Fatty Acids in Adipose Tissue-Derived from Wild Animals; A Pilot Study - Jadwiga Hamulka (MDPI AG, 2021)
The aim of this work was to study the quality (oxidative stability), fatty acids (FAs) profile and their distribution in triacylglycerol (TAG) molecules of hunted game wild fat (HGWF) obtained from wild boar, badger, and wild goose. Health lipid indices were calculated. The determination of FAs composition was carried out by gas chromatographic analysis of fatty acid methyl esters (FAME). Enzymatic hydrolysis and thin layer chromatography were used to determine the positional distribution of FAs in the internal and external positions of triacylglycerols (the regiospecific structure of triacylglycerols) of the obtained HGWF. A pressure differential scanning calorimeter (PDSC) was used to determine the oxidative stability of tested HGWF. The lipid fraction isolated from subcutaneous adipose tissues was dominated by MUFA, on average 46–50% of total FAs, and by SFA, on average 32–36% of total FAs. Palmitic acid was located mainly in the internal position of TAGs of the analyzed HGWF, whereas external positions were occupied by unsaturated oleic acid. Such a structure is responsible for normal fat absorption from food and it prevents the formation of insoluble calcium salts. Considering FAs profile, quality and the oxidation stability among all tested fat samples, the boar fat seems to be the most favorable.